Post-pandemic Evaluation on Housing and Its Influence on Future Healthy Housing Preferences - Bunga Sakina (DIMENSI (Journal of Architecture and Built Environment), 2025)
Post-COVID-19 pandemic, the topic of healthy housing continues to develop, one of which is related to the mental health of residents. The purpose of this study is to conduct a post-pandemic evaluation on Indonesian residents' housing satisfaction (HS), frequency of activities (FoA) during quarantine, and residents' future housing preferences (HP) that promote positive mental health. This study also tries to see the causal relationship between the variables influencing certain housing preferences. This quantitative study used an online questionnaire to collect and analyze data quantitatively using multivariate regression analysis. The results showed values for housing preferences were higher than housing satisfaction values. The causal relationships with the strongest influences are FoA daily on HP environmental comfort, HS physical space on HP physical space, and HS acoustic & visual comfort on HP semi-outdoor space. In general, HS acoustic & visual comfort and FoA daily were the most influencing on residents' preferences.